2013
DOI: 10.4103/0253-7176.116247
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome in drug-naïve patients with Depressive Disorders

Abstract: Background:The prevalence of metabolic syndrome (MS) is found to be higher in patients with depression than in the general population. As there is lack of data from India, this study aimed to assess the prevalence of MS in patients with depression who had never been treated with antidepressants for their depressive disorder and compare the same with a matched group of healthy controls.Materials and Methods:Forty-three drug-naïve patients with depressive disorders and 43 age- and gender-matched healthy controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Overall, we identified 31 eligible studies for inclusion in this meta‐analysis (Tables S3 and S4) (Arranz et al, ; Basoglu et al, ; Cai et al, ; Canan et al, ; Chang et al, ; Chen et al, ; Chen et al, ; Dasgupta, Singh, Rout, Saha, & Mandal, ; Enez Darcin, Yalcin Cavus, Dilbaz, Kaya, & Dogan, ; Fernandez‐Egea et al, ; Garcia‐Rizo et al, ; Garcia‐Rizo et al, ; Grover, Nebhinani, Chakrabarti, Avasthi, & Kulhara, ; Kavzoglu & Hariri, ; Keinanen et al, ; Leo et al, ; Misiak et al, ; Nyboe, Vestergaard, Moeller, Lund, & Videbech, ; Petrikis et al, ; Ryan et al, ; Saddichha, Manjunatha, Ameen, & Akhtar, ; Saloojee, Burns, & Motala, ; Sengupta et al, ; Spelman et al, ; Turan, Kesebir, & Suner, ; van Nimwegen et al, ; Venkatasubramanian et al, ; Wani et al, ; Wu et al, ; Yildirim et al, ; Zhang et al, ). Of these studies, one was conducted with patients who had a first episode mania (Turan et al, ), five were conducted with patients who had first episode depression (Canan et al, ; Chang et al, ; Garcia‐Rizo et al, ; Grover et al, ; Leo et al, ) and one was conducted with patients who had first episode mania or depression (Garcia‐Rizo et al, ). Twenty‐four were conducted in patients with FEP (Arranz et al, ; Basoglu et al, ; Cai et al, ; Chen, Broqueres‐You, et al, ; Chen, Du, et al, ; Dasgupta et al, ; Enez Darcin et al, ; Fernandez‐Egea et al, ; Kavzoglu & Hariri, ; Keinanen et al, ; Misiak et al, ; Nyboe et al, ; Petrikis et al, ; Ryan et al, ; Saddichha et al, ; Saloojee et al, ; Sengupta et al, ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, we identified 31 eligible studies for inclusion in this meta‐analysis (Tables S3 and S4) (Arranz et al, ; Basoglu et al, ; Cai et al, ; Canan et al, ; Chang et al, ; Chen et al, ; Chen et al, ; Dasgupta, Singh, Rout, Saha, & Mandal, ; Enez Darcin, Yalcin Cavus, Dilbaz, Kaya, & Dogan, ; Fernandez‐Egea et al, ; Garcia‐Rizo et al, ; Garcia‐Rizo et al, ; Grover, Nebhinani, Chakrabarti, Avasthi, & Kulhara, ; Kavzoglu & Hariri, ; Keinanen et al, ; Leo et al, ; Misiak et al, ; Nyboe, Vestergaard, Moeller, Lund, & Videbech, ; Petrikis et al, ; Ryan et al, ; Saddichha, Manjunatha, Ameen, & Akhtar, ; Saloojee, Burns, & Motala, ; Sengupta et al, ; Spelman et al, ; Turan, Kesebir, & Suner, ; van Nimwegen et al, ; Venkatasubramanian et al, ; Wani et al, ; Wu et al, ; Yildirim et al, ; Zhang et al, ). Of these studies, one was conducted with patients who had a first episode mania (Turan et al, ), five were conducted with patients who had first episode depression (Canan et al, ; Chang et al, ; Garcia‐Rizo et al, ; Grover et al, ; Leo et al, ) and one was conducted with patients who had first episode mania or depression (Garcia‐Rizo et al, ). Twenty‐four were conducted in patients with FEP (Arranz et al, ; Basoglu et al, ; Cai et al, ; Chen, Broqueres‐You, et al, ; Chen, Du, et al, ; Dasgupta et al, ; Enez Darcin et al, ; Fernandez‐Egea et al, ; Kavzoglu & Hariri, ; Keinanen et al, ; Misiak et al, ; Nyboe et al, ; Petrikis et al, ; Ryan et al, ; Saddichha et al, ; Saloojee et al, ; Sengupta et al, ...…”
Section: Resultsmentioning
confidence: 99%
“…For the fasting blood glucose analysis, 32 outcomes were extracted from 30 studies (Arranz et al, ; Basoglu et al, ; Cai et al, ; Canan et al, ; Chang et al, ; Chen, Broqueres‐You, et al, ; Chen, Du, et al, ; Dasgupta et al, ; Enez Darcin et al, ; Fernandez‐Egea et al, ; Garcia‐Rizo et al, ; Garcia‐Rizo et al, ; Grover et al, ; Kavzoglu & Hariri, ; Keinanen et al, ; Leo et al, ; Misiak et al, ; Nyboe et al, ; Petrikis et al, ; Ryan et al, ; Saddichha et al, ; Saloojee et al, ; Sengupta et al, ; Spelman et al, ; Turan et al, ; van Nimwegen et al, ; Venkatasubramanian et al, ; Wani et al, ; Wu et al, ; Yildirim et al, ; Zhang et al, ). In our overall analysis, there was no significant difference on fasting glucose levels between patient and control groups (ES = 0.10, CI = −0.03‐0.23).…”
Section: Resultsmentioning
confidence: 99%
“…[19] This is comparable to the prevalence found in our patients group (26% in recurrent depression and 24% in bipolar depression group). In another study done on drug-naive patients[37] of depression in India, the prevalence of MetS was found to be significantly higher (37.2%) than healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…This has been reported in many of the studies. [243741424344] Over the last 10–15 years, an increasing amount of literature has appeared, examining the cross-sectional and longitudinal relationship between the constructs of obesity and depression. While a large number of these studies have defined obesity by BMI, which is an indicator of general fat distribution.…”
Section: Discussionmentioning
confidence: 99%
“…There was a weak association between depression and low high-density lipoprotein cholesterol, but not with other component criteria of the metabolic syndrome (Foley DL et al, 2010). 26 Among Indian studies one crosssectional study found 37% of the depressed patients had MS, wherein their age, sex matched healthy counterparts' prevalence of MS was 16.3% and this difference was significant (Grover S et al, 2013). 27 Among our patients 16(31.4%) had metabolic syndrome, whereas in controls it was 8 (17.4%).…”
Section: Discussionmentioning
confidence: 99%